Dark triads, tetrads, tents, and cores: Why navigate (research) the jungle of dark personality models without a compass (criterion)? - Christopher Marcin Kowalski (Elsevier, 2021)
This comprehensive review summarizes and evaluates the present state of the Dark Triad research literature (or more broadly, the dark personality trait literature), and as such serves both a pedagogical purpose, by providing an introduction or primer on the dark personality literature and a scientific purpose by directing future research on key issues that still have not been sufficiently addressed. In this review, we discuss and critique current operational conceptualizations of what it means for a personality trait to be classified as ‘dark’. Also discussed is the Dark Core, as well as quantitative issues such as limitations of commonly used statistical treatments, such as multivariate analyses, bifactor modeling, and composite measures, and proposed solutions to some of these issues. Based on a comprehensive and critical appraisal of the literature, future directions are suggested to drive the dark trait field towards a more organized, parsimonious, and productive future.